1999
DOI: 10.1038/sj.ejhg.5200318
|View full text |Cite
|
Sign up to set email alerts
|

Genetic refinement and physical mapping of a chromosome 18q candidate region for bipolar disorder

Abstract: Recent genetic studies have implicated chromosome 18 in bipolar disorder (BP) with putative loci in the pericentromeric region and on 18q. We reported linkage to chromosome 18q21.33-q23 in a large family. In this study we typed additional markers in the family and were able to reduce the candidate region significantly. All affected family members are sharing alleles for markers spanning a genetic distance of maximal 8.9 cM. Haplotype analysis provided a marker order in agreement with published genetic and phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…12 In further studies we refined the linkage region at 18q21-q22, identified by De Bruyn et al in a multiplex Belgian BP family, 6 to an 8.9 cM region between D18S68 and D18S979 at 18q21-q22 and constructed a physical map using yeast artificial chromosomes (YACs). 13 Our candidate region at chromosome 18q21-q22 identified in the Belgian study overlaps with that reported by Stine et al 2 Several studies have described anticipation in families transmitting BP disorder, [14][15][16] suggesting the involvement of trinucleotide repeat expansions (TREs). Support for the involvement of CAG/CTG repeat expansions in BP disorder was obtained by the use of the repeat expansion detection (RED) method.…”
Section: Introductionsupporting
confidence: 50%
“…12 In further studies we refined the linkage region at 18q21-q22, identified by De Bruyn et al in a multiplex Belgian BP family, 6 to an 8.9 cM region between D18S68 and D18S979 at 18q21-q22 and constructed a physical map using yeast artificial chromosomes (YACs). 13 Our candidate region at chromosome 18q21-q22 identified in the Belgian study overlaps with that reported by Stine et al 2 Several studies have described anticipation in families transmitting BP disorder, [14][15][16] suggesting the involvement of trinucleotide repeat expansions (TREs). Support for the involvement of CAG/CTG repeat expansions in BP disorder was obtained by the use of the repeat expansion detection (RED) method.…”
Section: Introductionsupporting
confidence: 50%
“…The size and stability of the three YACs had previously been confirmed by PFGE. 2 Metaphase FISH and fiber FISH experiments confirmed that the three YACs are non-chimeric and overlapping (Figure 2). …”
Section: Mapping Of Known Cag/ctg Repeatsmentioning
confidence: 69%
“…To analyse the involvement of CAG/CTG repeats in the aetiology of BP disorder linked to 18q21.33-q23, we determined the localisation of eight known CAG/CTG repeats 2 The possibility that CAG/CTG repeats were missed by the YAC fragmentation was excluded by (CAG) 10 screening of cosmid sublibraries. No additional CAG/CTG repeats were isolated confirming that the CAG/ CTG YAC fragmentation is a sensitive method.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations